Exploring College Students' Attitudes towards English Language Learning in Nepal - Chand, Gambhir Bahadur (ILAM इलम, 2026)
This study explored college-level students' attitudes, perceptions, and motivation toward learning English. The data were collected via online structured questionnaire in a Google form which was sent to two hundred students through email and social media. Data were analyzed using statistical tools such as frequency and percentage. The findings reveal a positive attitude toward English language learning, high motivation and enthusiasm, confidence, and recognition of its value for academic, professional, and personal growth. Emotional and psychological engagement emerged as a critical factor in language acquisition, while instrumental motivation, particularly regarding career opportunities, played a significant role. The study also found the importance of English in personality development and continued academic development. The findings of this study line up with established theories in second language acquisition, emphasizing the role of motivation and engagement in language learning. The implications suggest the need for interactive and communicative instructional approaches, confidence-building activities, and career-oriented English courses. By addressing these factors, educators can enhance language learning outcomes and better prepare students for academic and professional success.